Progress in EBV Vaccines - van Zyl, Dwain G.; Mautner, Josef; Delecluse, Henri-Jacques (Frontiers in Oncology, 2019)
The Epstein-Barr virus (EBV) is a ubiquitous pathogen that imparts a significant burden of disease on the human population. EBV is the primary cause of infectious mononucleosis and is etiologically linked to the development of numerous malignancies. In recent years, evidence has also been amassed that strongly implicate EBV in the development of several autoimmune diseases, including multiple sclerosis. Prophylactic and therapeutic vaccination has been touted as a possible means of preventing EBV infection and controlling EBV-associated diseases. However, despite several decades of research, no licensed EBV vaccine is available. The majority of EBV vaccination studies over the last two decades have focused on the major envelope protein gp350, culminating in a phase II clinical trial that showed soluble gp350 reduced the incidence of IM, although it was unable to protect against EBV infection. Recently, novel vaccine candidates with increased structural complexity and antigenic content have been developed. The ability of next generation vaccines to safeguard against B-cell and epithelial cell infection, as well as to target infected cells during all phases of infection, is likely to decrease the negative impact of EBV infection on the human population.